2021
DOI: 10.3390/electronics10182225
|View full text |Cite
|
Sign up to set email alerts
|

Study of 3D-Printed Dielectric Barrier Windows for Microwave Applications

Abstract: 3D printing technologies offer significant advantages over conventional manufacturing technologies for objects with complicated shapes. This technology provides the potential to easily manufacture barrier windows with a low reflection in a wide frequency band. Several 3D printing methods were examined for this purpose, and the dielectric properties of the various types of materials used for 3D printing were experimentally studied in the frequency range 26–190 GHz. These measurements show that the styrene-butad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where: a 0 =-1.294�10 10 , a 1 = 1.725�10 10 , b 1 = 4.598�10 8 , a 2 = À 4.309�10 9 , b 2 = À 2.298�10 8 , ω = 0.0004298, and the result is shown graphically, Figure 4. Linear model "Poly3" (polynomial of the 3rd order):…”
Section: Numerical Examplesmentioning
confidence: 97%
See 1 more Smart Citation
“…where: a 0 =-1.294�10 10 , a 1 = 1.725�10 10 , b 1 = 4.598�10 8 , a 2 = À 4.309�10 9 , b 2 = À 2.298�10 8 , ω = 0.0004298, and the result is shown graphically, Figure 4. Linear model "Poly3" (polynomial of the 3rd order):…”
Section: Numerical Examplesmentioning
confidence: 97%
“…Further, a 3D-printed horn antenna, executed with high dielectric materials, is an example of the practical implementation of the technology [9]. A study of 3Dprinted dielectric barrier windows for microwave applications demonstrated that the studied technique can fabricate windows with a reflection level below À 18 dB in the frequency band up to 160 GHz but without analysis of the degradation properties [10]. Since many investigations need some numerical prediction (to validate whether is it necessary to perform an experiment), numerical modeling of 3D printed materials plays an important role in research on materials' degradation [11].…”
Section: Literature Surveymentioning
confidence: 99%